CORRELATION BETWEEN EFL STUDENTS’ PERCEIVED LINGUISTIC PROFICIENCY AND THEIR LEVEL OF CONFIDENCE IN USING ENGLISH - Amro, Mohammad Suleiman Mohammad; Maniam, Mahendran (English Department of Faculty of Tarbiyah and Teacher Training, 2019)
The main aim of this study is to find out the correlation between EFL students? perceived linguistic proficiency and their level of confidence in using English. To achieve that, sixty first year students at the faculty of English language and literature, Ajloun University in Jordan, were selected based on convenience sampling. The subjects were asked to self-assess their linguistic proficiency using five-point Likert scale and to respond to the survey questionnaire. To test the statistical associations between the two variables, ANOVA was used to confirm if there were any statistically significant differences in self- assessment scores among the groups of students having different levels of confidence. To confirm where the differences lie, Post Hoc tests (Turkey HSD and Homogeneous Subsets) were used. NOVA gives an F value of 44.131 with 2 and 57 degrees of freedom (p < 0.01), showing that there are differences in self-assessment means among groups. The multiple comparisons among mean differences by the Post Hoc tests (Turkey HSD and Fisher?s LSD) show that the group of students who are 'hardly confident' are significantly different from the other two groups of students. The group of students who are 'a little confident' are significantly different from 'hardly confident' students and 'confident' students. Finally, the group of students who are 'confident' differ significantly from the two groups of students who are 'hardly confident' and ?a little confident?. Therefore, all groups differ from one another. The results of the Kendall's tau-b and Spearman's rho indicate that there is a statistically significant correlation between the students' confidence level and the means of self-assessment scores. In conclusion, the subjects having high self-assessment scores are more likely to have high confidence in using English and vice versa.